Pedagogy and Psychology as Sciences for the Formation of the Potential of Modern Society - Nikolina V. V., Aksenov S. I., Zulkharnaeva A. V., Loshchilova A. A., Fefelova O. E., Frolova S. V., Koniushenko S. M., Komissarova M. O., Smykovskaia T. K., Petrova T. M., Plashchevaia E. V., Utochkina E. A., Prozorova M. N., Arefeva S. A., Arefeva O. V., Selivanova M. E., Pokhilko A. D., Kazachenko O. A., Zanin D. S., Golubeva M. M., Moiseeva K. S., Sudakov O. V., Sudakov D. V., Gordeeva O. I., Sych G. V., Rusina E. V., Kniazeva E. G., Akhmadeeva E. V., Biriukova I. A., Miriutsa E. V., Polushkina I. V., Topilskaia O. A., Iureva T. V., Uvarov E. A. (Pedagogy and Psychology as Sciences for the Formation of the Potential of Modern Society, 2024)
the chapter is devoted to the study of some aspects related to psychological and pedagogical support of medical students using the example of the Voronezh State Medical University named after N.N. Burdenko (VSMU named after N.N. Burdenko). This topic is becoming increasingly relevant every year due to the ever-increasing stress factors, including those leading to the development of depressive states and even suicide attempts, which is especially relevant among young people. The objects of the study were 200 students, men and women, of the medical faculty of VSMU named after N.N. Burdenko. All of them were divided into 2 groups depending on the course of study: group 1 included 100 1st year students, the second – 100 6th year students. The study is based on a questionnaire specially developed by the authors, including both general questions about gender, age, and special ones concerning awareness of some aspects of psychological and pedagogical support for students, as well as finding out the general attitude to psychological and pedagogical support and directly to the psychological service. The need for psychological assistance from school years to university years was studied, and cases of visiting specialists of this kind were analyzed. In addition, the number of students exposed to stress in life, school, and university was studied. Interesting features of the study were the analysis of the strongest stress factors for students of both groups, as well as the analysis of positive aspects, according to students, of psychological and pedagogical support for students. The data obtained in the chapter are of particular interest not only for psychological services and psychologists directly, but also for higher education teachers involved in the educational process with students and medical residents.
Keywords: студент; психолого-педагогическое сопровождение; врач; стресс; stress; student; psychological and pedagogical support; doctor; лечебный факультет; medical faculty